Question Number 114668 by bemath last updated on 20/Sep/20

((x+(√(x^2 −1)))/(x−(√(x^2 −1)))) + ((x−(√(x^2 −1)))/(x+(√(x^2 −1)))) = 98

Answered by som(math1967) last updated on 20/Sep/20

(((x+(√(x^2 −1)))^2 +(x−(√(x^2 −1)))^2 )/(x^2 −((√(x^2 −1)))^2 ))=98  ⇒((2(x^2 +x^2 −1))/1)=98  ⇒2x^2 −1=49  ⇒x^2 =((50)/2)  x=±5 ans

Commented bybemath last updated on 20/Sep/20

gave kudos

Commented bysom(math1967) last updated on 20/Sep/20

Is the langage from Indonesia?

Commented bybemath last updated on 21/Sep/20

no sir